PC concepts - Martin, Edward G.; Parker, Charles S. 1945- (Dryden Press series in information systems, 2000)
[This text is] created to provide a highly compact and current presentation of the world of PCs for students taking a first course in computers. It contains the knowledge one absolutely needs to know to understand how PCs work and how they can be used to maximum benefit. [The text discusses] such topics as storage and processing concepts, types of computer systems, PC hardware, PC software, communications systems fundamentals the Internet and the World Wide Web, shopping for a PC, and social issues regarding technology.